IDENTIFYING THE CULTURE OF THE MUHAMMADIYAH ISLAMIC BOARDING SCHOOL - Mardalis, Ahmad; Ahmadi, Mirzam Arqy; Shobahiya, Mahasri; Saleh, Minhayati (International Journal of Educational Management and Innovation, 2021)
This study aims to determine the organizational culture at the Muhammadiyah Islamic Boarding School. This research method includes qualitative research with the object of research is the Islamic Boarding School Modern Imam Syuhodo Sukoharjo. This study's collection method was obtained by seeking information from high-ranking informants and distributing questionnaires filled out by respondents at the Muhammadiyah Islamic Boarding School. Data collection techniques are carried out by interview, observation, and documentation supported by OCAI instruments. The results of the Leadership Research show that from the point of view of the leadership's assessment of the current dominant organizational culture, namely clan culture (40) and hierarchy (23). The data obtained shows that there is a significant difference between clan and hierarchy. The research results concluded that clan is the dominant culture for the current organizational culture and the dominant culture for the expected culture. At the same time, the hierarchy becomes the dominant culture in the second position. Then the organization needs a greater sense of kinship and better regulations to maintain organizational stability.